'It is life threatening but I don't mind'. A qualitative study using photo elicitation interviews to explore adolescents' experiences of renal replacement therapies. Issue 4 (8th June 2012) - Wells, F.; Ritchie, D.; McPherson, A. C.
Abstract Background Renal replacement therapy (RRT) transforms the life prospects of young people with established renal failure. However, these treatments can have significant physiological and psychological implications for adolescents as they prepare to transition into adulthood. Health policies increasingly emphasize children and youth's active participation and consultation as users of health services, yet studies infrequently seek their experiences directly. Methods Adolescents receiving RRT in a large UK teaching hospital took photographs illustrating the impact of their condition and treatment on their lives. Qualitative photo elicitation interviews were conducted to explore the significance of the images and the young person's experiences. Interviews were analysed using descriptive thematic analysis. Results Ten young people aged 13–17 years participated. Themes identified were: (1) understanding and acceptance of treatment; (2) living in a non‐functioning body; (3) impact upon daily life; (4) sources of support. Young people found treatments challenging and experienced significant impact on relationships and daily routines. Yet, health was prioritized over body image and participants demonstrated great emotional resilience. Young people valued support from family and friends, although were wary of disclosing their condition in case it resulted in being highlighted as different. Young people reported hospital staff as being caring and professional, but their biggest virtue appeared to be their willingness to treat the young people as 'normal'. Conclusions Young people engaged readily with the research, and frankly described the impact of RRT on their everyday lives. Service providers must ensure that adolescents' developmental needs are met as traditional tasks of adolescence may lose priority. However, it is also clear that young people's ability to cope with treatments should not be underestimated.